Bagaimana Seharusnya Top Management Merespon Whistleblowing ? Refleksi dari Sikap Kepemimpinan Mahapatih Gajah Mada : Refleksi dari Sikap Kepemimpinan Mahapatih Gajah Mada - Agustin, Henri (Owner : Riset dan Jurnal Akuntansi, 2024)
Research publications examining how top management should respond when whistleblowing occurs in organizations are still limited. The accuracy of the management response to whistleblowing is fundamental, because it can affect whether it will be repeated in the future or not. The accuracy of the management response to whistleblowing is determined by figures who can be used as role models. This research aims to explain Gajah Mada's leadership attitude that can be guided by top management responding to whistleblowing. The novelty of this research lies in presenting a new perspective in whistle blowing research, in the form of adopting leadership attitudes or values from great national figures as role models in responding to whistle blowing. This research is an interpretive study, utilizing literature related to Gajah Mada, Negara Kertagama, and whistleblowing as objects of observation. The literature search was conducted using a number of keywords such as "whistleblowing", "leadership+attitude+of+ Gajah Mada", "CEO+response to wrong doing report+fraud", or "CEO+reaction to wrong doing report+fraud". The data obtained is analyzed through 3 stages, namely identification, reflection, and synthesis. This interpretive study explains that top management can adopt 3 leadership attitudes of Gajah Mada, namely mantriwira, nayaken musuh, and wicaksaneng naya in responding to whistleblowing cases. It is important for top management to internalize the three attitudes